2020
DOI: 10.1590/1517-869220202606215617
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pituitary Dysfunction in Retired Professional Soccer Players

Abstract: Introduction: It is well-known that pituitary dysfunction can develop as a result of traumatic brain injuries. One reason for such injuries is collision during contact sports. Objectives: The aim of this study was to investigate the effects of heading the ball and concussion on pituitary function in retired soccer players. Methods: Thirty-two retired soccer players, with an average age of 43.38 ± 5.49 (35-59) and 26 sedentary individuals with an average age of 43.31±6.38 (35-59) were included in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Nine studies investigated the effects of RSHI on the hormonal response (see Additional file 1: Table S7), with the median sample size of 22 (range 11 to 68) contact sport athletes. One case study reported the acute semi-acute effects of RSHI on hormone levels in a kickboxer [113], and eight studies reported the chronic effects [100,103,104,107,111,[114][115][116]. Five studies that examined the chronic effects of RSHI in boxing and American football revealed growth hormone secretory deficiencies [103,104,114,115], anti-hypothalamus and anti-pituitary antibodies presence [116], insulin-like growth factor 1 [103,114] and adrenocorticotropic hormone [114,115] deficiency, and hypogonadism [104].…”
Section: Hormonal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies investigated the effects of RSHI on the hormonal response (see Additional file 1: Table S7), with the median sample size of 22 (range 11 to 68) contact sport athletes. One case study reported the acute semi-acute effects of RSHI on hormone levels in a kickboxer [113], and eight studies reported the chronic effects [100,103,104,107,111,[114][115][116]. Five studies that examined the chronic effects of RSHI in boxing and American football revealed growth hormone secretory deficiencies [103,104,114,115], anti-hypothalamus and anti-pituitary antibodies presence [116], insulin-like growth factor 1 [103,114] and adrenocorticotropic hormone [114,115] deficiency, and hypogonadism [104].…”
Section: Hormonal Studiesmentioning
confidence: 99%
“…Five studies that examined the chronic effects of RSHI in boxing and American football revealed growth hormone secretory deficiencies [103,104,114,115], anti-hypothalamus and anti-pituitary antibodies presence [116], insulin-like growth factor 1 [103,114] and adrenocorticotropic hormone [114,115] deficiency, and hypogonadism [104]. RSHI exposure in soccer players revealed no long-term effects on hormonal responses [100,111]. Overall, sustained exposure to RSHI appears to increase the risk of pituitary dysfunction in contact sport athletes.…”
Section: Hormonal Studiesmentioning
confidence: 99%